The Dynamics of Employee Roles in Collaborating on the Distribution of ZIS Bank Syariah Indonesia and LAZNAS BSI Maslahat through Digital Platforms - Phatriakalista Intan Apsari; Yuli Budiati; Rohmini Indah Lestari (Universitas Mercu Buana, 2026)
This study examined the role of employees and obstacles in the distribution process of zakat, infaq, and sadaqah (ZIS) funds based on a digital platform, as wall as strategies to improve the effectiveness of ZIS fund distribution performance. Previous research has primarily focused on conventional systems and has not yet extensively examined the role of employees in managing the distribution of ZIS through integrated digital platforms across institutions. The focus of the study was directed at the collaboration between Bank Syariah Indonesia and its strategic partner in managing ZIS funds, namely LAZNAS BSI Maslahat. This study used a qualitative phenomenological approach. Data was obtained through in-depth interviews with informants, this was supported by documentation such as the ZIS assistance application process and reports on the realization of assistance distribution. Data analysis used the Miles & Huberman model, with source triangulation and technique triangulation. The results of the study show that the distribution of ZIS funds through digital platforms is carried out through a clear division of functional roles with the support of cross-functional digital coordination. However, the dual roles at the BSI Branch and Area levels have caused delays in the administrative completion of fund distribution. The findings reveal that the system is not the main obstacle, but rather the management of roles that determines the effectiveness of distribution. Therefore, this study suggests strengthening human resources through cross-functional digital coordination as the basis for formulating strategies to improve the effectiveness of ZIS fund distribution.